2006
DOI: 10.1007/s10661-006-9283-9
|View full text |Cite
|
Sign up to set email alerts
|

Variations and trends of ground-level ozone and AOT40 in the rural areas of Lithuania

Abstract: The analysis of data of the ground-level ozone concentration and accumulated ozone exposure over a threshold of 40 ppb (AOT40) in the rural areas of Lithuania is presented. Trends in the annual ozone mean, 95th and 25th percentiles were determined as statistically not significant at Preila and Rugsteliskes sites during the 1994-2004 period. Trends in the ozone concentration and its percentiles in the air masses arriving to Preila station in "polluted" and "unpolluted" sectors have been examined. Statistically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 8 publications
(8 reference statements)
0
12
0
Order By: Relevance
“…These changes in O 3 concentrations were typical for other parts of Central Europe (Bytnerowicz et al 2002;Bytnerowicz et al 2004;Solberg et al 2005). Higher ozone concentrations were mostly observed when air masses were transported from western Europe (Girgzdiene et al 2007). X XI XII I II III IV V VI VII VIII IX X XI XII I II III IV V The seasonal variation in air pollutant concentrations and acid deposition resulted in different significances in the relationships of the considered pollutants and pine stand defoliation.…”
Section: Seasonal Variability Of Air Temperature and Precipitation Anmentioning
confidence: 99%
“…These changes in O 3 concentrations were typical for other parts of Central Europe (Bytnerowicz et al 2002;Bytnerowicz et al 2004;Solberg et al 2005). Higher ozone concentrations were mostly observed when air masses were transported from western Europe (Girgzdiene et al 2007). X XI XII I II III IV V VI VII VIII IX X XI XII I II III IV V The seasonal variation in air pollutant concentrations and acid deposition resulted in different significances in the relationships of the considered pollutants and pine stand defoliation.…”
Section: Seasonal Variability Of Air Temperature and Precipitation Anmentioning
confidence: 99%
“…The earlier investigations [16] have shown that the main source of the ground-level ozone concentration at the Preila station is the transport of ozone from other locations but not the local photochemical production. Therefore, in our study we have assumed that the ozone lifetime in the environment of this station is mainly determined by the ozone transport from higher layers to the ground-level through air turbulence, and destruction at the Earth's surface but not by the chemical loss.…”
Section: Modellingmentioning
confidence: 93%
“…The ozone concentration in Lithuania mostly varies up to 100-120 µg m -3 [7], and the level of 120 µg m -3 is observed only during less than 10% of time per year and it is usually the result of long-range transport of polluted air [7]. It is also estimated [8,9] that during the sea breeze circulation ozone concentration can rise up to a high level.…”
Section: Introductionmentioning
confidence: 99%